Methylene Blue-Catalyzed Oxidative Cleavage of N-Carbonylated Indoles - Wu, Kui; Fang, Cheng; Kaur, Sarbjeet; Liu, Peng; Wang, Ting (Synthesis, 2018)
The development of a visible-light-mediated oxidative cleavage of electron-deficient indoles is reported. Methylene blue serves as an effective catalyst and the transformation shows a broad substrate scope. A variety of functional groups are well accommodated in the mild reaction conditions. The photo-mediated single electron transfer and oxidative cleavage mechanisms were investigated via density functional theory and Marcus theory calculations.
Keywords: methylene blue; visible light; electron-deficient indoles; Witkop–Winterfeldt oxidation; photocatalysis